2019
DOI: 10.1177/0363546519885104
|View full text |Cite
|
Sign up to set email alerts
|

Graft Size and Orientation Within the Femoral Notch Affect Graft Healing at 1 Year After Anterior Cruciate Ligament Reconstruction

Abstract: Background: The combined influence of anatomic and operative factors affecting graft healing after anterior cruciate ligament (ACL) reconstruction within the femoral notch is not well understood. Purpose: To determine the influence of graft size and orientation in relation to femoral notch anatomy, with the signal/noise quotient (SNQ) of the graft used as a measure of graft healing after primary single-bundle ACL reconstruction. Study Design: Case series; Level of evidence, 4. Methods: A total of 98 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 38 publications
3
30
1
Order By: Relevance
“…If this occurs after a return to pivoting sports, there are multiple possible causative patient factors or technical failures. It could be a repeat of a significant mechanism of injury similar to rupture of a native ACL, poor muscular or dynamic control of the limb, 15 insufficient 19 or excessive 22 amount of graft, positioning of the graft, 3 or, with the present study, higher graft signal indicating incomplete healing and integration of the graft. Appearances of high signal at the Figure 5.…”
Section: Graft Rupturementioning
confidence: 63%
See 2 more Smart Citations
“…If this occurs after a return to pivoting sports, there are multiple possible causative patient factors or technical failures. It could be a repeat of a significant mechanism of injury similar to rupture of a native ACL, poor muscular or dynamic control of the limb, 15 insufficient 19 or excessive 22 amount of graft, positioning of the graft, 3 or, with the present study, higher graft signal indicating incomplete healing and integration of the graft. Appearances of high signal at the Figure 5.…”
Section: Graft Rupturementioning
confidence: 63%
“…The present study used the same suspensory fixation on both the tibial and the femoral sides, yet significantly higher signal was seen on the femoral side. This has been recognized before, with a number of possible explanations: a more acute graft-bending angle proximally as the graft enters the joint 25 ; the potential for femoral notch impingement, especially if there is a graft-notch mismatch 22 ; or a femoral tunnel placed closer to the posterolateral bundle origin. 16 This study adds to previous evidence that suggests that the proximal femoral-sided graft may be the rate-dependent area for healing of the entire graft.…”
Section: Variation In Mri Appearance Across the Graftmentioning
confidence: 87%
See 1 more Smart Citation
“…Femoral tunnel malposition is 3 times more frequent than tibial tunnel malposition [33]. In our study, the femoral tunnel position was measured with the use of Bernard quadrant method, which was applied in several studies [5,27]. The anatomic position of the femoral tunnel socket for single-bundle ACLR is de ned in line with the study of Xu et al [22].…”
Section: Discussionmentioning
confidence: 93%
“…Graft healing may be affected by tunnel position as well. Oshima et al [27] reported low femoral tunnel was one of the factors signi cantly associated with high graft signal/noise quotient value, which indicated inferior graft healing. On the other hand, the study of Novaretti et al [28] proved that de cit of quadriceps strength did not predict return to preinjury level of sport at 6 months postoperatively, which were consistent with the outcomes of 12 months after surgery in our study.…”
Section: Discussionmentioning
confidence: 99%